FROM SCROLLING TO STRUCTURING: THE ROLE OF MOBILE AI TOOLS IN IDEA GENERATION FOR ESL WRITING AMONG GENERATION Z LEARNERS - Muratova Khurshida Ne’matullo qizi (TADQIQOTLAR, 2025)
Abstract The shift to mobile-assisted learning has dramatically influenced writing instruction in English as a Second Language (ESL) classrooms, especially among Generation Z learners. This paper explores how mobile-based AI tools, specifically ChatGPT, serve as catalysts for idea generation in ESL writing instruction. Grounded in digital learning theories and constructivist pedagogy, the study examines practical classroom applications of ChatGPT on mobile devices and surveys learners’ perceptions. The findings suggest that mobile AI tools help ESL students overcome idea-generation blocks, promote learner autonomy, and enhance cognitive engagement. Pedagogical implications and ethical considerations are discussed.